2019
DOI: 10.3390/jcm8071032
|View full text |Cite
|
Sign up to set email alerts
|

Role of Combined [68Ga]Ga-DOTA-SST Analogues and [18F]FDG PET/CT in the Management of GEP-NENs: A Systematic Review

Abstract: Gastro-entero-pancreatic neuroendocrine neoplasia (GEP-NENs) are rare tumors, but their frequency is increasing. Neuroendocrine tumors normally express somatostatin (SST) receptors (SSTR) on cell surface, especially G1 and G2 stage tumors, but they can show a dedifferentiation in their clinical history as they become more aggressive. Somatostatin receptor imaging has previously been performed with a gamma camera using [111In]In or [99mTc]Tc-labelled compounds, while [68Ga]Ga-labelled compounds and PET/CT imagi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(56 citation statements)
references
References 54 publications
0
56
0
Order By: Relevance
“…Contrary to patients with evident SCLC or widespread metastatic disease (194), in the context of occult EATs some experts recommend performing the 18 FDG PET/CT scan after Octreoscan or 68 Ga -SSTR PET/ CT (146). The claimed rationale for justification of this attitude is that occult tumors are often non-metastatic and that well-differentiated NETs are characterized by their slow growth rate, factors that theoretically could result in negative 18 FDG -PET imaging (195). However, metaanalysis of Isidori et al (146) reported that 18-FDG PET/CT, performed in fewer than a hundred EAS patients, identified the responsible NET in nearly 52% of cases.…”
mentioning
confidence: 99%
“…Contrary to patients with evident SCLC or widespread metastatic disease (194), in the context of occult EATs some experts recommend performing the 18 FDG PET/CT scan after Octreoscan or 68 Ga -SSTR PET/ CT (146). The claimed rationale for justification of this attitude is that occult tumors are often non-metastatic and that well-differentiated NETs are characterized by their slow growth rate, factors that theoretically could result in negative 18 FDG -PET imaging (195). However, metaanalysis of Isidori et al (146) reported that 18-FDG PET/CT, performed in fewer than a hundred EAS patients, identified the responsible NET in nearly 52% of cases.…”
mentioning
confidence: 99%
“…Besides 18F-DOPA PET/CT, the most widely used PET technique for NEN imaging is SSTR PET/CT using gallium-68-somatostatin analogues (i.e., DOTA-NOC, DOTA-TOC, or DOTA-TATE). Recent meta-analysis shows high diagnostic accuracy in this setting [29,30]. The use of F-18-FDG-PET/CT is usually limited to patients with high G2 or G3 tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, LDH was one of the impactful prognostic factors identi ed in this study. The characteristics of NECs, such as high glucose consumption, high lactate production, a hypoxic tumor environment because of poor vascularization, and high proliferation, could increase LDH levels [15,17,18].…”
Section: Discussionmentioning
confidence: 99%